2018
DOI: 10.1016/j.pec.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

To support and to be supported. A qualitative study of peer support centres in cancer care in Norway

Abstract: Objective: To explore what peer supporters, patients and their relatives want and gain from peer support in cancer care. Methods:Focus group interviews with peer supporters, and in-depth interviews with peer supporters, patients and relatives (N=38) and observations of daily activities in a Vardesenter ("Cairn Centre").Results: Peer supporters helped cancer patients and relatives with coping in and outside the hospital in several ways: (1) conveying hope and providing ways to cope in situations where despair w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 30 publications
5
32
0
1
Order By: Relevance
“…First, PAs may benefit from their role as a peer supporter, and the role becomes a part of their own long-term psychological recovery. This has been confirmed in previous studies where peer supporters achieve a positive impact by putting their own disease trajectory and life experiences into perspective [14,19,21]. Second, PAs represent a selected group of peers who are psychologically robust, which is important as those who wish to participate are best suited for the role of peer supporter.…”
Section: Discussion Of Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…First, PAs may benefit from their role as a peer supporter, and the role becomes a part of their own long-term psychological recovery. This has been confirmed in previous studies where peer supporters achieve a positive impact by putting their own disease trajectory and life experiences into perspective [14,19,21]. Second, PAs represent a selected group of peers who are psychologically robust, which is important as those who wish to participate are best suited for the role of peer supporter.…”
Section: Discussion Of Resultssupporting
confidence: 66%
“…Peer support may benefit not only the person being supported but also the supporter [14,15]. Peers possess an understanding and a first-hand experience of the disease and its treatment, and may provide support to a peer who is at an earlier stage of treatment or recovery [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional support included conveying hope and ways of coping (25,29), reducing loneliness (27), and improving self-esteem (34). Peer support helps people communicate with partners and family members (29).…”
Section: What Are the Benefits Or Risks Of Peer Support?mentioning
confidence: 99%
“…However one study comparing online and face to face groups concluded that face to face groups were better for exchanging information and caring for others (46). Socially, peer support was seen as providing a framework for social comparisons (25), where exchanging thoughts was easier with a peer (27), and with a need for mutual identification (36). Being a peer supporter was felt to be positive and important, giving people a sense of achievement (25,26).…”
Section: What Are the Benefits Or Risks Of Peer Support?mentioning
confidence: 99%